Home interventions and light therapy for treatment of vitiligo (HI-Light Vitiligo Trial): study protocol for a randomized controlled trial - Haines, Rachel H.; Thomas, Kim S.; Montgomery, Alan A.; Ravenscroft, Jane C.; Akram, Perways; Chalmers, J.R.; Whitman, Diane; Duley, Lelia; Eleftheriadou, Viktoria; Meakin, Garry; Mitchell, Eleanor; White, Jennifer; et al. (BMJ Publishing Group Ltd, 2018)
Vitiligo is a condition resulting in white patches on the skin. People with vitiligo can suffer from low self-esteem, psychological disturbance and diminished quality of life. Vitiligo is often poorly managed, partly due to lack of high quality evidence to inform clinical care. We describe here a large, independent, randomised controlled trial (RCT) assessing the comparative effectiveness of potent topical corticosteroid, home-based hand-held narrowband ultraviolet B-light (NB-UVB) or combination of the two, for the management of vitiligo.